Pemberdayaan Masyarakat melalui Pengembangan Pariwisata dari Produk Anyaman Berbasis Budaya di Desa Tua di Kabupaten Buleleng Bali - Nyoman Gede Mas Wiartha; A.A. Istri M. Septiviari; I Made Sucipta Adnyana; Dewa Gde Ngurah Byomantara; Made Darmiati (PT. PENERBIT TIGA MUTIARA, 2026)
Cultural-based tourism has become an important strategy for enhancing community welfare while preserving local cultural heritage. Desa Tua in Buleleng Regency, Bali, possesses significant potential through the bamboo weaving tradition of the Bali Aga community, which holds substantial economic and cultural value. This study aims to analyze community empowerment through the development of tourism based on cultural weaving products, strengthen the bargaining position of local artisans, and examine efforts to maintain a balance between economic benefits and cultural preservation. The study employed a mixed-methods approach with a sequential explanatory design and involved 150 respondents. Data were collected through observation, interviews, documentation, and surveys. The findings reveal that experiential tourism increased average household income by 35% and enhanced women's participation by 42% through their involvement in production activities, training programs, tour guiding, and the management of creative enterprises. Traditional weaving products were successfully developed as the primary tourism attraction, generating greater economic value while preserving cultural integrity through the clear distinction between sacred and commercial products. The utilization of digital media further expanded market access and strengthened product competitiveness. The novelty of this study lies in the development of an integrative model that connects community empowerment, experiential tourism, cultural preservation, women’s empowerment, and digital cultural entrepreneurship as a sustainable strategy for cultural tourism development.